2023
DOI: 10.1111/ene.15899
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical evolution of patients with prolonged disorders of consciousness due to severe anoxic brain injury: A meta‐analytic study

Abstract: Background and purposeThe prognosis of prolonged (28 days to 3 months post‐onset) disorders of consciousness (pDoC) due to anoxic brain injury is uncertain. The present study aimed to evaluate the long‐term outcome of post‐anoxic pDoC and identify the possible predictive value of demographic and clinical information.MethodThis is a systematic review and meta‐analysis. The rates of mortality, any improvement in clinical diagnosis, and recovery of full consciousness at least 6 months after severe anoxic brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Sex of the patients emerged as a significant predictive factor for the outcome, though with a rather moderate effect size. While previous studies on the effect of sex have yielded inconsistent results, 16,17,26 a recent large meta-analysis aligns with our findings, 32 suggesting that male patients, particularly husbands, may receive more effective care from their spouses than female patients. Although this factor can be real, it might result in a higher mortality rate among females rather than in an increased recovery rate in males.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Sex of the patients emerged as a significant predictive factor for the outcome, though with a rather moderate effect size. While previous studies on the effect of sex have yielded inconsistent results, 16,17,26 a recent large meta-analysis aligns with our findings, 32 suggesting that male patients, particularly husbands, may receive more effective care from their spouses than female patients. Although this factor can be real, it might result in a higher mortality rate among females rather than in an increased recovery rate in males.…”
Section: Discussionsupporting
confidence: 87%
“…Some recent large-scale clinical trials and a meta-analysis concluded that younger patients recover more frequently. 6,17,31,32 We were unable to confirm this Cumulative incidence (%) finding in the overall sample. However, our additional analysis revealed that older patients die earlier and more frequently than younger patients.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation